2020
DOI: 10.31557/apjcp.2020.21.10.3115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Possible Association between PD-1 (Rs11568821, Rs2227981, Rs2227982) and PD-L1 (Rs4143815, Rs2890658) Polymorphisms and Susceptibility to Breast Cancer in a Sample of Southeast Iranian Women

Abstract: Introduction: Programmed cell death-1 (PD-1) and its ligands (PD-L1 and PD-L2) play a critical role as a regulator of immune-system cells, including T cell, natural killer T (NKT), monocytes, dendritic cells (DC), and B cells. Objective: This study aimed to find a possible association between PD-1 (rs11568821, rs2227981, rs2227982), and PD-L1 (rs4143815, rs2890658) variants and Breast Cancer (BC) risk in a sample of southeast Iranian women. Method: The case-control study consisted of 520 individuals, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…It could also be speculated that the frequency of exhausted PD-1 + T cell subpopulations that can be reinvigorated by anti-PD-1 blockade may differ between individuals based on the presence of certain PD-1 germline polymorphisms but functional effects of PD1.3 in the cancer setting remains to be established. Of interest, several population-based studies conducted largely in the Asian population and meta-analysis of available data have shown a significantly lower cancer risk associated with the PD1.3 (rs11568821) SNP ( 8 , 27 , 28 ), while other studies could not confirm these findings ( 29 ). The risk for the development of melanoma and the here examined SNPs is unclear, and we have not been able to find well annotated WGS data in sufficiently large cohorts of melanoma patients to cross-reference observed-to-expected minor allele frequency (MAF) as derived from the 1000 Genomes project.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be speculated that the frequency of exhausted PD-1 + T cell subpopulations that can be reinvigorated by anti-PD-1 blockade may differ between individuals based on the presence of certain PD-1 germline polymorphisms but functional effects of PD1.3 in the cancer setting remains to be established. Of interest, several population-based studies conducted largely in the Asian population and meta-analysis of available data have shown a significantly lower cancer risk associated with the PD1.3 (rs11568821) SNP ( 8 , 27 , 28 ), while other studies could not confirm these findings ( 29 ). The risk for the development of melanoma and the here examined SNPs is unclear, and we have not been able to find well annotated WGS data in sufficiently large cohorts of melanoma patients to cross-reference observed-to-expected minor allele frequency (MAF) as derived from the 1000 Genomes project.…”
Section: Discussionmentioning
confidence: 99%
“…Our population-based case-control study consists of 520 individuals, including 260 histologically confirmed BC patients and 260 age-matched population-based healthy women with no history of any type of cancer and (samples are not related to the patients of the study). The protocol of this study has been designed based on previous investigations (Danesh et al, 2018;Karami et al, 2020). The Institutional Review Board approved this study to be conducted at the Zahedan University of Medical Sciences (IR.ZAUMS.REC.1397.385).…”
Section: Patientsmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (RT-PCR) was performed as described previously (Hashemi et al 2013;Karami et al 2020). Briefly, the cells were covered with specific concentrations of 5-FU (10 and 1.25 μM), D4476 (5 μM), and the combination of 5-FU and D4476 for 24, 48, and 72 h. The total RNA was isolated by the RNX-Plus RNA extraction kit (Cinnagen, Iran), following the manufacturer's instruction, and then RNA quantity and quality were assessed by electrophoresis and a Nano Drop spectrophotometer (Thermo Scientific, USA) (260/280 nm ratio).…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%